Study JIC and crack evolution behavior of as-cast steel at elevated temperatures. (September 2015) - Zhang, Jian; Chen, Deng-Fu; Zhang, Cheng-Qian; Hwang, Weng-Sing
Abstract: In this paper, the critical value of J -integral ( JIC ) of as-cast steel is measured at elevated temperatures by using a Gleeble 1500D thermomechanical simulator. The JIC value and plastic deformation power Upl decrease with temperature increases. Specifically, with measured temperature at 700 °C, 800 °C and 900 °C, the respective values of JIC are 37.13 N/mm, 27.94 N/mm and 15.05 N/mm. Moreover, the detailed analyses of fracture surface show ductile fracture at elevated temperatures. The large tear dimples appear at crack initiation stage and the dimples are shallow in the early stage of crack stable propagation, and deeper later in the stage. The dimple size increases according to the load time. Highlights: The critical value of J -integral ( JIC ) of as-cast steel is measured at elevated temperatures. The large tear dimples appear at crack initiation stage. The dimples are shallow in the early stage of crack stable propagation, and deeper later in the stage.